Identifikasi Bakteri Endofit Pada Daun Sirih (Piper betle L.) Dengan Metode 16S rRNA - Prasetya, Eko; Damanik, Joshua Leonard (Journal of Natural Sciences, 2025)
Betel leaf (Piper betle L.) is a plant that has antibacterial properties, and is one of the plants that can be used as a source of endophytic bacteria. Endophytic bacteria can produce the same secondary metabolites as the host plant. In identifying bacteria, the 16S rRNA gene is used This study aims to identify endophytic bacterial species that were successfully isolated from betel leaves using the 16S rRNA method.The betel leaves taken are old leaves. The methods used are laboratory research methods and literature studies. Laboratory methods include isolation and molecular identification of endophytic bacteria. The literature study method is to look for previous research results in the form of journals, books, articles and compare them with the laboratory isolation results obtained. The results of molecular identification of endophytic bacteria have 99.81% similarity to Lysinibacillus fusiformis strain N169 (IE 1), 100% similarity to Pseudomonas aeruginosa strain PaLo22 (IE 2), and 100% similarity to Bacillus cereus strain Z2-R9 (IE 3). It can be concluded that there are 3 endophytic isolates that have been successfully isolated with various macroscopic and microscopic diversity.